PROTOTYPE PARKING SENSOR ON A SHIP AT THE DOCK USING SENSOR BASED ON ARDUINO UNO R3 - Candli, Candli; Pernando, Yonky (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
The main issue that needs to be addressed in this research is to enhance the safety and efficiency of the vessel berthing process by reducing the risk of collisions with the dock. With the advancement of technology in the maritime industry, there is still a reliance on various parties such as tugboats, ship crew, and dock authorities to ensure safe vessel berthing. Therefore, it is necessary to design a modern technology-based parking sensor system to provide assistance in the vessel berthing process. By using a parking sensor system based on the Arduino Uno R3 and ultrasonic sensors JSN-SR04T and AJ-SR04M, this research aims to address the risk of collisions with the dock, which can result in serious damage to the vessel, dock, and the surrounding environment. This parking sensor system is designed to reduce this risk by providing early warnings to the users. Furthermore, the research aims to reduce dependence on human factors and minimize human errors. Lastly, the research also aims to improve the efficiency of the vessel berthing process. By designing and implementing this prototype, the research aims to provide a technological solution to address the above-mentioned issues, enhance safety, and optimize the vessel berthing process around Motor Vessel BIN NO.2 EKS. SANYO MARU NO.8.